Evidence of Distinct Channel Conformations and Substrate Binding Affinities for the Mitochondrial Outer Membrane Protein Translocase Pore Tom40 - Kuszak, Adam J. (J Biol Chem, 2015)
Nearly all mitochondrial proteins are coded by the nuclear genome and must be transported into mitochondria by the translocase of the outer membrane complex. Tom40 is the central subunit of the translocase complex and forms a pore in the mitochondrial outer membrane. To date, the mechanism it utilizes for protein transport remains unclear. Tom40 is predicted to comprise a membrane-spanning β-barrel domain with conserved α-helical domains at both the N and C termini. To investigate Tom40 function, including the role of the N- and C-terminal domains, recombinant forms of the Tom40 protein from the yeast Candida glabrata, and truncated constructs lacking the N- and/or C-terminal domains, were functionally characterized in planar lipid membranes. Our results demonstrate that each of these Tom40 constructs exhibits at least four distinct conductive levels and that full-length and truncated Tom40 constructs specifically interact with a presequence peptide in a concentration- and voltage-dependent manner. Therefore, neither the first 51 amino acids of the N terminus nor the last 13 amino acids of the C terminus are required for Tom40 channel formation or for the interaction with a presequence peptide. Unexpectedly, substrate binding affinity was dependent upon the Tom40 state corresponding to a particular conductive level. A model where two Tom40 pores act in concert as a dimeric protein complex best accounts for the observed biochemical and electrophysiological data. These results provide the first evidence for structurally distinct Tom40 conformations playing a role in substrate recognition and therefore in transport function.